LINGUA LEGIS IN HUNGARIAN-POLISH AND POLISH-HUNGARIAN TRANSLATION - KACZMAREK, Karolina (Comparative Legilinguistics, 2017)
The main aim of the work is to present techniques of providing equivalence for Polish and Hungarian legal texts at the level of texts, syntagmas and words. The research results have been divided into three main parts. The first part touches upon the historical development of Hungarian legal language in the light of the development of the Hungarian law. The second part starts with the chapter about general rules concerning statutory instruments and their translation, the next chapter is devoted to the structure of statutes, especially some distinctive words and sytagmas, which are used in selected types of statutory provisions. The third part treats about the structure of Polish and Hungarian documents which were executed for the purpose of legal proceedings. The author suggests how to translate them into Hungarian and Polish respectively. The results of this research can be used in the theory and practice of translation of Polish and Hungarian legal texts.